(untitled) (Global Journal of Science Frontier Research, 2014)
An effective understanding of water and sanitation supply in developing states such as Edo- state is a veritable tool in addressing uneven distribution of these utilities. This research study focuses on the evaluation of water and sanitation supply in the state using baseline and demand responsiveness approaches to capture data on water and sanitation supplies in all the 18 local government areas in the State. Variables such as coverage of access or no access to water and sanitation supply, sources of water and incidences of water-related diseases were captured and technically analysed. The output of the analysis revealed that 62% representing 1,346, 649, population could not access portable water, while 38% corresponding to 813,199 could fairly access portable water in 1993. However, coverage for safe drinking water between 1993 and 2002 in Edo-State is not significant at 95% confidence interval. In addition, 72% (2,009,566 population) did not have any access to sanitation; while 28% (777,210 population) had fair supply of sanitation. The regions with poor sanitation and water index are Etsako central, Etsako west, Esan west, Esan north-west, while Oredo, Akoko-Edo, Egor and Owan east have improved sanitation and water index. The results obtained also indicate widespread of water and sanitation related diseased in the State with the recorded highest cases of Schistosomaisis (134, 361:43%); Typhoid (81,981:27%); Cholera (62,191:20%) and Diarrhea (29,893:10%) respectively.